Assessment of the technical competence and ethical behaviour of community-based animal health workers in Mwingi District, Kenya - Rubyogo, Jean-Claude; Murithii, PM; Agumbah, G.J.O.; Obhai, G (Springer, 2005)
This paper describes an assessment of the technical competence and ethical behaviour of Community-based Animal Health Workers (CAHWs) in Mwingi District, Kenya. From 99 trained CAHWs, 40 participated in the study. Using a pre-tested semi-structured questionnaire, direct observation of the relevant veterinary drug kits and participatory discussions, the study team found that the CAHWs knowledge of clinical signs of local livestock diseases and notifiable and zoonotic diseases and their ability to use veterinary drugs correctly and safely were adequate. Marks were awarded to the candidates according to an agreed marking scheme between the CAHWs’ trainers and study team members. The results showed that, overall, 36 out of 40 (90%) of the sampled CAHWs passed the tests. The existence of a referral system for CAHWs and refresher trainings helped to ensure that CAHW competence and ethical behaviour were maintained. However, it was also found that some areas of the current curriculum required more detailed input based on field experience. The CAHW system could serve as an alternative animal health care system in areas lacking veterinary services.